2019
DOI: 10.1093/advances/nmy130
|View full text |Cite|
|
Sign up to set email alerts
|

A Global Review of Food-Based Dietary Guidelines

Abstract: The objective of this review is to provide a concise, descriptive global review of current food-based dietary guidelines (FBDG), and to assess similarities and differences in key elements of a healthy diet articulated across countries. Information was sourced from the FBDG repository of the FAO, which catalogs FBDG for all countries where they are available, including a description of the food guide (the graphic representation of the dietary guidelines), a set of key messages, and downloadable documents provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
496
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(526 citation statements)
references
References 14 publications
24
496
1
5
Order By: Relevance
“…School closures have led to distance-learning and home-schooling-not to mention challenges to food distribution: school is the place where many children around the globe get a consistent daily caloric intake. School-based nutrition is a reality in both developing and developed countries [7][8][9]. Parents are experiencing increased pressure to work from home, to keep jobs and businesses running, as well as to support, educate and comfort their children at the same time.…”
Section: Open Accessmentioning
confidence: 99%
“…School closures have led to distance-learning and home-schooling-not to mention challenges to food distribution: school is the place where many children around the globe get a consistent daily caloric intake. School-based nutrition is a reality in both developing and developed countries [7][8][9]. Parents are experiencing increased pressure to work from home, to keep jobs and businesses running, as well as to support, educate and comfort their children at the same time.…”
Section: Open Accessmentioning
confidence: 99%
“…Many countries, including the United States, have food-based dietary guidelines that include recommendations for food group consumption [43]. The majority of countries that have food-based dietary guidelines use five food groups, including starchy staples (grains for MyPlate in the United States), fruits, vegetables, dairy foods, and protein foods.…”
Section: Diet Qualitymentioning
confidence: 99%
“…Findings from this study indicate that guidance on snacks will be an important consideration as dietary guidelines are developed specifically for young children below two years of age. Though currently limited [36], national food-based dietary guidelines with specific recommendations for infants and young children are increasing and serve as an opportunity to aid caregivers in their snack-feeding practices. The complementary feeding period stretches from 6 months until 2 years of age, and is a period marked not only by the introduction of solid foods but the transition from 'baby' foods to 'family' foods [52]; food-based dietary guidelines could provide caregivers additional guidance on the types of family foods that are appropriate or inappropriate for young children.…”
Section: Discussionmentioning
confidence: 99%
“…Governments in both New Zealand and Australia have recently published dietary guidelines for infants and toddlers, and in both publications, snacks fed between meals are recommended alongside the recommendation to choose snacks containing limited salt and added sugar [35,63]. A recent global review of 90 food-based dietary guidelines found that while general guidance to limit salt and sugar intakes were nearly universal, only 28% of all national guidelines included messages to limit intakes of processed foods, such as unhealthy snack foods or beverage products [36]. There is a clear need for countries to expand food-based dietary guidelines for the complementary feeding period and to include guidance that can moderate consumption of nutrient-poor, unhealthy snack foods and beverages among young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation